Alliance motives towards dynamic capabilities and the competitiveness of healthcare organizations - Al Kaabi, Khaled Mohammed Rashed Salem (2023)
Strategic alliance is increasingly gaining attention in healthcare service provision. However, there is a lack of understanding on alliance motives among healthcare institutions and how they affect several aspects of healthcare organizations’ dynamic capabilities and competitiveness. The aim of the present study is to identify alliance motives and critically examine how they drive the competitiveness of the UAE healthcare organizations. Contextualised within the UAE healthcare sector, this study adopted a mixed methods research design, which involved two phases. In the first phase, a qualitative research method driven was conducted to identify and describe alliance motives and the dynamic capabilities of the healthcare organizations. For this purpose, a semi-structured interview with 25 alliance project leaders located in the Abu Dhabi and Dubai healthcare organizations was conducted. In the second phase, a quantitative method using a survey was conducted to examine the relationship between alliance motives, value-based dynamic capabilities and healthcare institutions’ competitiveness. A sample of 279 employees of healthcare institutions responded to the survey questionnaire and the data were analysed using Amos. The finding revealed that alliance motives driven by transactional cost economy, industry-relationship and partners competencies are important factor for the development of healthcare dynamic capabilities, particularly in coordination, integration and reconfiguration capabilities, which influence healthcare institutions’ competitiveness. This research provides an integrative model that explains how to improve alliance motives towards value creation in the dynamic capabilities, which consequently improve alliance competitive performance. This research is one of the few researches explores how knowledge sharing drives strategic alliances practices that contribute to competitive performance of the UAE healthcare institutions.